INTERNATIONAL COOPERATION IN THE FIELD OF CULTURE UNDER THE CONDITIONS OF THE RUSSIAN-UKRAINIAN WAR: CULTURAL ASPECT - Maslikova, Iryna (Ukrainian Cultural Studies, 2023)
The article analyzes the experience of international cooperation in the field of culture during the Russian-Ukrainian war. Significant achievements in international cooperation by the means of culture resulted in the institutionalization of cultural diplomacy as a tool of the cultural policy of "soft power". Cultural diplomacy includes the exchange of ideas, information, and cultural goods between peoples in order to foster mutual understanding. Thanks to the United24 platform and the Ukrainian Institute, large-scale projects have been implemented last year. These projects aimed at helping victims of war, their rehabilitation, rebuilding cultural infrastructure, Ukraine’s involvement in weighty cultural events and processes, and the presentation of Ukrainian culture to the world. Informational, volunteer, rehabilitation, sanctions, diplomatic activities in the field of culture in wartime conditions proved that cultural diplomacy is an effective tool of cultural, humanitarian and security policies. Realization of the main goal of Ukrainian cultural diplomacy – the expansion of Ukraine’s recognition abroad is impossible without awareness of the value basis of Ukrainian culture and the belonging of the Ukrainian people to a broad cultural and political context. The issue of the cultural identity of Ukrainians is connected with the colonial past of Ukraine, the aggressive expansion of Russia. The revaluation of the cultural role of Russia gained urgent relevance against the background of the war and, on the one hand, led to the practices of "the cancel culture". This practice is important to ensure that there are no attempts to apparently balance the victims of Ukrainians and Russians in the war, the anonymity of the true victims and the lack of fair retribution for criminals, the silencing of the truth, and war fatigue. On the other hand, such processes aggravated the issue of various "others", who will be able to unite on the basis of a common contemporary Ukrainian culture after the war. Therefore, in order to clarify the specifics of cultural identity, a number of cultural problems arise that require a theoretical solution (the nature of cultural identity, the constitution of cultural subjectivity in the conditions of imperialism and post-colonialism, cultural prejudices, national imagination, "the cancel culture", revaluation of the cultural role of Ukraine). Cultural studies of these issues will strengthen the discussions around the issues of a better political order and the formation of post-colonial cultural policy in Ukraine.